Análise do conhecimento de acadêmicos de pedagogia de uma universidade pública a respeito da utilização de técnicas adequadas de primeiros socorros em pediatria - MARTINS, Elciane Calandrino (2020)
Accidents that occur during childhood are one of the most common causes of morbidity and mortality in the world, becoming a serious public health problem. This work aimed to know the level of knowledge of the pedagogy students of the Federal University of Pará regarding first aid techniques. From the methodological point of view, this study is a quantitative, analytical, cross-sectional research. The study was conducted at the Faculty of Pedagogy of the Federal University of Pará (UFPA). Eighty-one students of the pedagogy course participated in this research. Of these 58.03% were attending the 7th semester and 41, 97% were attending the 8th semester. All research participants attend teaching internships. Of these, 88.89% are in their first degree and 11.11% are in their second degree. Regarding the interviewees´ age, they were between 20 and 47 years old and the average was 27.59 years old. When asked about conducting a first aid training course, 12.35% students answered “Yes”, 85.19% answered “No” and only 2.46% didn’t answer the question. Regarding the importance of first aid instruction for the training of future education professionals, 98.77% answered “Yes” and only 1.23% answered “No”. It was asked whether during the academic training some first aid workload was provided, only 3.70% answered "Yes" and 96.30% answered "No". About general knowledge in first aid we got 35.80% of hits and 64.20% of errors. Regarding the proper techniques of first aid in cases of poisoning we obtained 72.84% hits and 27.16% errors of the question. With respect to the proper first aid techniques in cases of OVACE, we obtained as a result 71.60% hits and 28.40% errors of the question. Regarding the proper techniques of first aid in cases of seizures we obtained 59.26% hits, 39.51% errors and 1.23% abstentions answer the question. Regarding the proper techniques of first aid in cases of burns, we obtained 62.97% of hits, 35.80% of errors and 1.23% refrained from answer the question. Regarding the proper techniques of first aid in cases of fracture, we obtained 54.33% hits, 44.44% errors and 1.23% abstention answer the question. Thus, the results of this study show that the knowledge of first aid by future child education professionals is extremely important, because the adequate first treatment provided to the child victim of accidents is essential for life maintenance and reduction of injuries, thus contributing to a better quality of life of the accident victim.